Inventory Control System and Profitability of Companies: A Study of Selected Listed Firms in Nigeria - Olaide, Anita Lewis; Omodero, Cordelia Onyinyechi (The Journal of Accounting and Management, 2023)
ABSTRACT Inventory management is critical to a company's efficient operations. Inventory management is a crucial aspect of profitability. The purpose of the study was to determine the impact of inventory management on the profitability of two (2) industrial goods firms listed on the Nigerian Stock Exchange. The independent variable (Inventory Management) was measured using opening inventory, closing inventory and average inventory. The dependent variable (Firm Profitability) was measured using Profit After Tax gathered for the study for a period of 5 years (2015-2019), was analysed using descriptive statistics, correlation analysis and ordinary least square method. The results of the study showed that inventory management had a significant effect on Profit After Tax. Therefore, the study recommends that in order for companies to improve on their Net Profits as a measure of profitability, they should implement strategies in order to improve their inventory management systems. Keywords: Inventory Management, Profitability.